Between Destiny And Selfishness: An Existential Study On Bella's Search For Meaning Of Life In Meyer's Breaking Dawn Novel (2008) - Setyanti, Ida Octaviana; , Dr. M. Thoyibi, M.S; , Nur Hidayat, S.Pd (2013)
This research paper elaborates about destiny and selfishness of Bella in Meyer's Breaking Dawn novel, which is analyzed through existentialist psychoanalytic perspective. The objectives of the researc h are to analyze the novel based on its structural elements and to analyze the novel especially the main character based on the existentialist psychoanalytic perspective. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is Breaking Dawn novel by Stephenie Meyer and the secondary data source is collected from other documents discussing about existentialist psychoanalytic, literary books, criticism, and articles related to the novel.The technique of analyzing data is descriptive analysis. The results of the study are as follows. First, based on the structural analysis it is apparent that in this novel, the author conveys a moral message that love and selfishness is sometimes indistinguishable. Second, based on the existentialist psychoanalytic analysis, the author illustrates a psychological phenomenon in which an individual is torn between two different qualities, whether she wants to make her life meaningful by becoming as she is, or to fulfill her wishes by becoming somebody other than herself.